Pengaruh Promosi Terhadap Tingkat Penjualan Mobil Sigra Pada PT. Astra International Tbk Daihatsu Cabang Malalayang - Yunita A. L. Labanu; Harry J. Sumampouw; Lucky F. Tamengkel (JURNAL ADMINISTRASI BISNIS, 2018)
The purpose of this study “whether the promotion effect on the level of sales of Sigra car at PT. Astra International Tbk Daihatsu branch Malalayang. The benefits in this study are 1.This research is expected to increase the treasury of science used as a reference material for the Department of Administrative Sciences in general and especially the Program of Business Administration Science in the marketing sector related to promotion and sales, 2.This research is expected to be a material information and input as well as brainstorming suggestions for leaders and employees of PT. Astra International Tbk Daihatsu Branch Malalayang as Daihatsu Dealer. The approach of this study was quantitative. The data sought from this research is sigra car sales data from the company and questionnaire data distributed to consumers. The result show that there is a significant influece because the value of t hitung 5,095 greater > t table value of 1,994 inferential that the hypothesis Ho rejected and accept HA. Based on the data obtained, it can be concluded that the influence of promotion on the level of Sigra car sales is at a strong enough correlation level of 27.3%, while 72.7% influenced by other factors not examined in this reseach.Keywords: Promotion, level of sales